Estimating the impact of ship strikes on the Mediterranean fin whale subpopulation. (15th April 2023) - Sèbe, Maxime; David, Léa; Dhermain, Frank; Gourguet, Sophie; Madon, Bénédicte; Ody, Denis; Panigada, Simone; Peltier, Hélène; Pendleton, Linwood
Abstract: The Mediterranean fin whale ( Balaenoptera physalus ) subpopulation is under threat from collisions with ships. Given the international dimension of the issue, the French, Italian, Monegasque and Spanish governments have proposed a Particularly Sensitive Sea Area (PSSA), i.e., a management zone of the International Maritime Organization (IMO), in which mandatory and voluntary protective measures can be implemented. Defining the risk and its impact at the subpopulation level is required to improve the chances of an IMO acceptance for such a proposal. While previous research partially succeeded in defining the collision risk, its impact on the subpopulation has not been thoroughly evaluated, especially at the spatial scale of the envisioned PSSA. Our study uses the carcass recovery approach to estimate the number of deadly collisions within the proposed PSSA. We then assess the probability that this number exceeds three management rules: Potential Biological Removal (PBR), Alert Reference Point (ARP) and Critical Reference Point (CRP). These management rules describe thresholds beyond which (a) the incidental mortality may prevent the recovery of the population within 100 years (PBR), (b) there is a cause for concern about incidental mortality (ARP), and (c) there is a critical need to lower the incidental mortality (CRP). We conclude that mortality from collisions alone is in excess of PBR. Taking into account confirmed and suspected collisions in strandings in calculations, the collision mortality exceeds ARP; this threshold being considered unacceptable by some international organisations. Additionally, there is almost a 35% chance that the mortality due to ship strikes exceeds the CRP, likely resulting in a population decline. The probability of anthropogenic mortality exceeding CRP is 60% if we include the fishery-related mortality in stranding (i.e., taking into account the total incidental mortality from bycatch and ship strikes). The PSSA proposal could use our approach to estimate the impact of collisions and assess the effectiveness of implemented protective measures. However, it is important to highlight that the IMO process for establishing a PSSA is lengthy, and our findings show that immediate action is required, as there is a high probability that the ship strike and fishery mortality is beyond the critical threshold fixed by the Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and contiguous Atlantic area (ACCOBAMS). Graphical abstract: Image 1